TANGGUNG JAWAB PELAKU USAHA TERHADAP KERUGIAN KONSUMEN PENGGUNA KRIM PEMUTIH BERBAHAYA YANG TIDAK BERLABEL BPOM - Nababan, Rosiana Pratiwi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Most of people see the woman’s beautiful face ftom the physical only, it make woman to try to do facial skin care. However, some business actor explot the situation and make foul. Some businesses add mercury and hydrokinon to product they distribute. Bleach cream that are not labeled BPOM, for example Temulawak and Natural 99 are still circulating in Pekanbaru. Based on constitution number 8 of 1999, drug and cosmetics store as one of business are responsible for guaranteeing the quality of goods trades. If there is a loss to the cunsumers. The purpose of the reseach are: First, to find out the responsibility for the loss of consumers using dangerous whitening cream in Pekanbaru. And secondly to find out what consumers are doing agains losses experienced by consumers using dangeous whitening cream in Pekanbaru.The method used is empirical research, another named is sosiological research. This observation, author use sosiological methods namely the study about effectiveness of the laws that apply in society and identify unwritten laws that apply in society. In this case the the reseacrhers conducted research on drug and cosmetics store in Pekanbaru, especially Senapelan district, Sukajadi district, Marpoyan Damai district and Pekanbaru Kota district. In collecting the data, the type of data used in this study are primary data and secondary data, directly via respondent (field). Constitution number 9 of 1999 on Consumer Protection, law journal and book related to the research. The data analysis was done qualitatively and conclusion drawn deductively.From the results of the research in this thesis, there are two main things that are concluded, namely First the form of the business actor’s responsibility towards the loss of consumers using dangerous face whitening creams in Pekanbaru. The second, the effort made by consumers towards the losses experiences by consumers using dangerous whitening creams in Pekanbaru.Keywords : Consumer – Responsibility – Business actor – Consumer Protection